CREAM LIQUEUR UVILLA FLAVOR (PHYSALIS PERUVIANA) - Paspuel, Dayana Jamileth (2020)
The uvilla is a fruit that expands in the agricultural field of Ecuador; this fruit is marketed fresh and a minimum percentage in processed fruits such as jam, puree and frozen pulp. The purpose of this project is to produce a liqueur cream flavored with uvilla, as a new alternative for industrialization in the province of Carchi; for which the drink is made by fermenting the uvilla juice for a period of 15 days, which was subsequently subjected to the simple distillation process, the degrees of alcohol were measured, then the uvilla sauce was made at a medium temperature. Once the alcohol is acquired, it is mixed with the other inputs (milk cream, uvilla sauce, uvilla alcohol), therefore, three treatments are carried out with different formulations, which a sensory analysis was applied to all treatments by means of 50 semi-trained tasters from the Universidad Politécnica Estatal del Carchi, a food engineering degree, he is able to determine which formulation has the greatest acceptance. The final product has 14 degrees of alcohol, which indicates that it is within the rules of the INEN 2802 STANDARDS; also a pH of 4.72 and 36 ° Brix; However, it is not a totally harmful drink, since it contains 40% milk cream and 30% uvilla sauce, which provide nutritional properties and health benefits